POLICE ACTIVITIES IN THE FIELD OF ROAD SAFETY MONITORING - Matvejevs, Aleksandrs (Administrative and Criminal Justice, 2018)
The legal problem of policing is how to regulate police powers that enable police officers to enforce laws. The purpose of this article is to investigate legal restrictions in police law. The author considers some legal restrictions implemented by the police in the field of road traffic.